2021
DOI: 10.3390/biom11010068
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Plant Origin on Eurasian Propolis on Phenolic Profile and Classical Antioxidant Activity

Abstract: Propolis is a bee product with known medical properties, including antioxidant activity. The scope of the study is profiling 19 different Eurasian propolis samples (mostly from Russia and Kazakhstan, Kyrgyzstan, Poland, Ukraine, and Slovakia). Profiles of propolises were investigated by ultra-high-performance liquid chromatography–diode array detector–mass spectrometry (UPLC-DAD-MS). Classical antioxidant properties, which are based on electron donation mechanism, were assessed by DPPH, ferric reducing antioxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
43
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(49 citation statements)
references
References 42 publications
5
43
1
Order By: Relevance
“…This hypothesis may be supported by the high amount of triterpenoids in HEP. Our results were consistent with previous studies [ 37 , 41 , 60 ]. However, our findings did not agree with other previous studies that demonstrated that polar solvents were better at extracting antioxidants from propolis and by extension improved the antioxidant properties compared with nonpolar solvents [ 15 , 61 ].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…This hypothesis may be supported by the high amount of triterpenoids in HEP. Our results were consistent with previous studies [ 37 , 41 , 60 ]. However, our findings did not agree with other previous studies that demonstrated that polar solvents were better at extracting antioxidants from propolis and by extension improved the antioxidant properties compared with nonpolar solvents [ 15 , 61 ].…”
Section: Discussionsupporting
confidence: 94%
“…The relationship between antioxidant activity and the chemical composition of propolis from different origins has been investigated by several groups [ 64 67 ]. These studies suggest that the high antioxidant activity of propolis is related to its high content of polyphenolic compounds, such as flavonoids [ 13 , 60 ]. This suggests that different compositions in different propolis samples may exhibit some similar functions, such as antioxidant activity.…”
Section: Discussionmentioning
confidence: 99%
“…The use of raw plant material and bee products for cosmetic and pharmaceutical purposes depends on cumulative polyphenols and their quantity. Bee products have been greatly valued since ancient times, especially propolis, as it is rich in phenolic acids and flavonoids [4,5]. Propolis was widely used for wound and skin care, for the treatment of bacterial and viral upper respiratory tract infections, for immune system strengthening and for the treatment of gastric problems [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Chrysin is thought to be involved in different biological mechanisms as it performs a protective role against oxidative stress, neurodegeneration, cancer, and inflammation. Okińczyc, et al [ 44 ] collected Eurasian samples of 19 different types of propolis, mainly from regions in Russia and Kazakhstan, Kyrgyzstan, Poland, Ukraine, and Slovakia. The propolis from poplar constituted chrysin, rutin, and apigenin.…”
Section: Discussionmentioning
confidence: 99%